Personalized versus partisan representation in the speeches of migrant members of parliament in the German Bundestag. Issue 9 (14th July 2020) - Bäck, Hanna; Debus, Marc
ABSTRACT: Given the increasingly polarized debates in many modern democracies over migration and integration, the behaviour of members of parliament (MPs) with a migrant background has important implications for patterns of representation. Drawing on role congruity theory, we hypothesize that MPs with a migrant background deliver more legislative speeches in debates that are of interest for citizens with a migrant background. The findings, which are based on speeches delivered in the German Bundestag between 2009 and 2013, indicate that MPs of immigrant origin, in particular those MPs who have a "visible" migrant background, deliver significantly more speeches in debates focusing on civil rights. We also find that migrant MPs who are elected via the party list, as opposed to MPs who are directly elected in a district, are more likely to speak in debates on citizen and minority rights, suggesting that the parliamentary party leadership strategically selects migrant MPs as speakers in certain parliamentary debates.